A scoping review protocol of the lived experiences of doing a PhD in Africa. - Oluwatomilayo Omoya; Udeme Samuel Jacob; Olumide A Odeyemi; Omowale A Odeyemi (PLoS ONE, 2023)
Objective This scoping review aims to investigate the available literature on the lived experiences of doing a PhD in African Universities. Introduction The continent of Africa still contributes a minimal amount of research towards global research outputs. The need for increased research capacity and outputs have been identified as priority for growth and development. There is a substantial need for evidence-based solutions that can alleviate some of these complexities. For example, challenges still exist in the disease burden faced, economic poverty and lack of infrastructure in various contexts. Methods and analysis Multiple databases will be searched, including the EBSCO Host, Scopus, EMBASE, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Medline (Ovid), and Google Scholar. The scoping review will be conducted using the Arksey & O'Malley (2005)'s six-step approach in conjunction with the Joanna Briggs Institute (JBI) methodology for scoping reviews. Studies that examined the perspective of PhD (Doctor of Philosophy) candidates, supervisors from Africa, and research studies focusing on the common barriers and facilitators concerning research in Africa will be included. Studies that explore the perspectives of other postgraduate cohorts will be excluded. Ethics and dissemination Ethics application will not be required but findings will be disseminated through publications, conference presentation, policy, and relevant stakeholders. Review registration number This study has been registered with the Open Science Forum (OSF).